Educational Psychological Counselling and Collective Competence Improvement Related to Autism/Autism Spectrum Disorders (ASD) - Kamil Özerk; Elise Öksendal; Meral Özerk (International Electronic Journal of Elementary Education, 2018)
A collective Competence Improvement Project (CIP) was conducted for educational psychological counselors (n=5) along with teachers (n=11), special education teachers (n=7), and child and youth workers (n=11). All of the participants were involved in the training and teaching of children with autism/ASD in a small municipality in Norway. The CIP focused primarily on competence improvement in the participants’ overall knowledge and theoretical conceptions about autism/ASD. Additionally, other goals included competence improvement in Discrete Trial Teaching (DTT), Pivotal Response Training (PRT), and Social Stories™ (SS). The results demonstrate that the CIP contributed to improvements in some of these targeted areas but not in all. Educational psychological counsellors and special education teachers benefited more and satisfactorily from the CIP than teachers and child and youth workers (CYWs). It is now clear that achieving significant improvement in competency does not necessarily equate to satisfactory improvement. Additionally, improving the professionals’ theoretical knowledge is important, but it does not necessary lead to improving their operational knowledge--their capacity for implementing their knowledge in practice. This paper presents the background, implementation, and results of the CIP, and it closeswith a discussion of the findings and conclusions about their implications for future CIPs and research.